Investigations into the relationship between changes in internal moisture regimes and rock surface deterioration in cavernous sandstone features. Issue 7 (12th December 2013) - Mol, Lisa
ABSTRACT Cavernous features commonly develop in sandstone, but their development over time remains enigmatic. It has been suggested that moisture movements within the rock mass play a key role in the location, development and dynamics of cavernous features. In this research the role of internal moisture movement is tested through monitoring moisture and surface deterioration dynamics in April 2008 and April 2009 within two large cavernous features (mega‐tafoni) in the Golden Gate Highlands National Park, South Africa (GGHNP). Data are presented from surveys of internal moisture (using electrical resistivity tomography, ERT), surface moisture (using a Protimeter) and deterioration (using surface hardness as recorded with an Equotip as a proxy for surface deterioration) across five 2.45 m long transects. In addition a high resolution temperature record is presented to assess the influence of micro‐climates within the caverns. The results indicate consistency in the gross spatial pattern of moisture flow within the rock mass over a one year period, but significant changes in mean moisture contents and in the fine detail of moisture patterning. Some noticeably weakened areas had developed within the central parts of the cavernous features, often linked to wetter subsurface conditions, supporting the theory that 'core softening' is a main driver of cavernous feature formation. However, in some areas surface hardening is also found to be associated with wetter subsurface conditions, supporting the theory that 'case hardening' is a main driver of cavernous feature formation. In addition, the presence of well‐established biofilms suggests an even more complex interaction between moisture, surface development and biological activity. A model is presented therefore which integrates this paradox by proposing a non‐linear relationship between moisture dynamics, facilitation of biofilm formation, and deterioration within cavernous features. Copyright © 2013 John Wiley & Sons, Ltd.